KORELASIONAL MOTIVASI KERJA TERHADAP GAJI DAN TUNJANGAN PADA CV. HABIBI DI DESA AWANG BANGKAL - Misransyah (Fekon Uvaya Banjarmasin, 2021)
Employees are one of the important resources, namely labor as a driver of other economic factors (production resources), such as money, materials, methods, machines, markets available and owned by the company. Planned, implemented, monitored and controlled by the company. Motivation is to revive the enthusiasm and passion of the potential and work ability of employees so that the needs and goals of each employee and business entity are achieved, in addition to the perception of interest in line with expectations, challenges and guarantees of certain continuous employment opportunities between employee needs and company goals, can be real fulfilled and sustainable. The research aims to determine the motivation to meet the work needs of employees in the form of salaries and benefits as well as to meet the interests and goals of the business entity. This research is useful as an employee performance survival that can be used as input for company management and limited liability companies in providing the desired motivation potential in the form of salaries and subsidy by CV. Habibi in Awang Bangkal Village. This study uses a survey method, with a population of 21 people. This study shows the employee motivation variable CV. Habibi In Awang Bangkal Village in terms of the salary and benefits of his employees.